Significant enhancement of electrochemical behaviour by incorporation of carboxyl group functionalized carbon nanotubes into polyaniline based supercapacitor. (October 2016) - He, Xinping; Liu, Guolong; Yan, Bo; Suo, Hui; Zhao, Chun
Graphical Abstract: Highlights: The polyaniline/carbon nanotube composite was fabricated for supercapacitors. The introduction of carboxyl group generates a sea cucumber structure. Carboxyl group functionalization enhanced electrochemical behaviour of composite. Abstract: The innovative sea cucumber like polyaniline/carbon nanotube-COOH (PANI/CNT-COOH) composite material achieves enhanced electrochemical properties, due to the carboxyl group functionalization on the surface of carbon nanotubes generates unique microstructure, conductivity and excellent electrical properties. Cyclic voltammetry and galvanostatic charge/discharge tests are carried out to investigate the electrochemical properties. The PANI/CNT-COOH material exhibits higher capacitance (381 F g −1 at 1 A g −1 ) than PANI/CNT (without carboxyl group functionalization, 238 F g −1 at 1 A g −1 ) and pure PANI (186 F g −1 at 1 A g −1 ). PANI/CNT-COOH also exhibits fast reflect of oxidation/reduction at high current density and good long-term cycling stability with capacity retention ratio of 92% after 1000 cycles. The three-dimensional (3D) structure provides a high electrode/electrolyte contact area and a short path length for electrons and electrolyte ions transport.